Brian Meeks, Envisioning Caribbean Futures - Jay R. Mandle; Brian Meeks; Rivke Jaffe (NWIG, 2011)
In this feature we highlight a recently launched book. We invite specialists in the field to comment on the book, and we invite the author to respond to their comments.

In this issue we focus on Brian Meeks's, Envisioning Caribbean Futures. Those invited to comment on the book are Jay Mandle and Rivke Jaffe.

[First paragraph]
In Envisioning Caribbean Futures: Jamaican Perspectives (2007), Brian Meeks writes “in sympathy with the new social movements that have evolved in the past decade which assert boldly that ‘another world is possible’” (p. 2). His effort is “to explore the horizons for different approaches to social living in Jamaica and the Caribbean in the twenty-first century” (p. 2). In this, he “seeks to move beyond a statement of general principles to propose specific alternatives” in order to “stimulate a conversation that looks beyond the horizon of policy confines, yet is not so far removed as to appear hopelessly utopian” (p. 3). My hope with this essay is to advance that conversation, in the first place by reviewing and assessing Meeks’s contribution and then by extending the discussion to the role that Jamaica’s diaspora (and by extension that of the region’s generally) might play in moving the country, as Meeks puts it, from its current “state of crime and murder, and the broad undermining of the rule of law that pervades the society” (p. 71).